Speed Control of Multiphase Cage Induction Motors Incorporating Supply Sequence - Drozdowski, Piotr (Archives of Electrical Engineering, 2014)
The subject of this paper is the control possibility of the multiphase cage induction motors having number of phases greater than 3. These motors have additional properties for speed control that distinguish them from the standard 3 phase motors: operation at various sequences of supplying voltages due to the inverter control and possible operation with few open-circuited phases. For each supply sequence different no load speeds at the same frequency can be obtained. This feature extends the motor application for miscellaneous drive demands including vector or scalar control. This depends mainly on the type of the stator winding for a given number of phases, since the principle of motor operation is based on co-operation of higher harmonics of magnetic field. Examples of operation are presented for a 9-phase motor, though general approach has been discussed. This motor was fed by a voltage source inverter at field oriented control with forced currents. The mathematical model of the motor was reduced to the form incorporating all most important physical features and appropriate for the control law formulation. The operation was illustrated for various supply sequences for “healthy” motor and for the motor operating at one phase broken. The obtained results have shown that parasitic influence of harmonic fields interaction has negligible influence on motor operation with respect to the useful coupling for properly designed stator winding.